The Effect of Developments During and After the Iraq War on Turkish-American Relations - Gürbüz, Kahraman (Journal of History Culture and Art Research, 2023)
Turkiye is one of the countries that the USA primarily takes into consideration while determining its policies especially in the Middle East, the Balkans, Caucasus and Central Asia. After the Second World War, the relations between Turkiye and the USA were shaped on the axis of their national security strategies. It has been argued that Turkiye’s importance especially for the USA and the Western countries has decreased by the disintegration of the Soviet Union. During and after the First Gulf War, which the USA started against Iraq within the scope of its policies towards the Middle East geography, Turkiye has been the country that most supported to the USA. The USA could not get the support it expected from Turkiye in the process of intervention of Iraq in 2003. During this process, the 1st March permit crisis, the Sulaymaniyah raid, the relations established between the USA and the Kurdish groups in Northern Iraq and the developments in this region against Turkiye adversely affected the relations between two countries. The attitude displayed by the USA that encourages and strengthens the PKK against Turkiye has increased the anti-US sentiment in the Turkish public opinion. The relations established between the USA and organizations that threaten Turkiye’s national security and territorial integrity have led to serious questioning of its strategic partnership or alliance with Turkiye. When the Syrian civil war and the intervention of imperialist countries in the region were added to the wars in Iraq, a vacuum of authority occurred on Turkiye’s southern border. Political uncertainties and social turmoil that have emerged in this direction have become a threat to the territorial integrity of Turkiye as well as its neighbors Iraq and Syria. In this study, the Permit Crisis, the Sulaymaniyah Raid and its impact on the USA and Turkiye during the intervention in Iraq and the effects of the developments in Northern Iraq on Turkiye’s fight against the PKK after the invasion are discussed. On the subject, some historical determinations, evaluations and various suggestions were made by making use of the research works and the national press, as well as the military sources.